'Entre journalisme et littérature sur 7 500 signes': Lance Armstrong and suiveur reporting in Libération, 1999–2013. (August 2020) - Dauncey, Hugh; Cooke, Ruadhán
As national institution and site of memory for France for over a century, the Tour de France is a privileged locus for investigating the interactions between sport and cultural meaning. Literary journalism chronicling the race has a long history of representing the multiple meanings and dimensions of physical performance, particularly of heroic champions, in the Tour. During the late twentieth and early twenty-first centuries the Tour itself and French culture more widely were destabilised by the ambiguous hero Lance Armstrong, and, in a context of guarded reporting on the facts of doping, literary journalism was able to give a creative account of complex sporting performances. This article examines the journalism of Jean-Louis Le Touzet in Libération as an example of suiveur reporting in the tradition of Antoine Blondin, and shows how the freedom of literary journalism allows Le Touzet to accurately reflect academic perspectives on Armstrong, politics, culture and sport.